Organic hole injection material and application thereof
Patent Information
- Application Number
- CN202211165979.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-09-23
AI Technical Summary
但具有合适的HOMO,LUMO能级的小分子比较少,选择范围小
[0043]The beneficial effects are as follows: The hole injection material provided by this invention is a double five-membered ring derivative substituted with electron-deficient groups. These double five-membered rings include, but are not limited to, thiophene, furan, or selenophenol double five-membered ring groups. The synthesis of such materials is relatively simple, which is beneficial for large-scale production; the material has suitable HOMO and LUMO energy level structures, which is conducive to carrier injection; the material's core of substituents and five-membered rings is beneficial for carrier transport in the device; and the material has high LUMO/HOMO energy levels, which is beneficial for transporting holes from the anode ITO to the hole transport layer.
Smart Images

Figure CN117800983B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic light emission, and more specifically to an organic hole injection material and its application. Background Technology
[0002] Organic light-emitting diodes (OLEDs), as a next-generation display technology, have gradually become an important component of current display technologies due to their numerous advantages such as self-illumination, flexibility, high contrast, and energy saving, and have received widespread attention from academia and industry. In OLED devices, the hole injection layer serves as a key material connecting the anode and the organic functional layer. It lowers the potential barrier for hole injection from the anode, enabling holes to be effectively injected into the OLED device. Therefore, when selecting the hole injection layer material, the matching of the material's energy levels with the anode material must be considered.
[0003] The role of the injection layer is to ensure a good match between the work function of the anode and the HOMO of the hole transport layer material, allowing holes to flow smoothly from the electrode to the transport layer. In fact, through OLED structure design, the highest occupied orbital energy level of the luminescent material is made close to the work function of the anode, reducing the hole injection energy barrier. A hole injection layer is usually added between the anode and the hole transport layer, mainly because the large energy barrier between them causes an increase in the device's driving voltage, indirectly shortening the device's lifespan. Therefore, adding a material with a HOMO energy level between the anode and the hole transport layer improves the efficiency between hole injection and the hole transport layer. Currently, hole injection materials used in optoelectronic devices can be divided into two categories: inorganic hole injection materials and organic hole injection materials. Inorganic hole injection materials are prone to reacting with organic layers at high temperatures, and their high evaporation temperature is unfavorable for the fabrication of organic optoelectronic devices. Organic hole injection materials can be further divided into small molecule hole injection materials and polymeric hole injection materials. Polymer hole injection materials are limited in their purity and cannot be fabricated into devices via vapor deposition. Small-molecule organic hole injection materials, on the other hand, offer very high purity and can be used to fabricate high-quality devices via vapor deposition. However, there are relatively few small molecules with suitable HOMO and LUMO energy levels, limiting the selection range. Therefore, it is necessary to develop novel and suitable organic small-molecule hole injection materials. Developing suitable hole injection materials plays a crucial role in improving the performance of OLED devices. Summary of the Invention
[0004] In view of the many shortcomings of existing hole injection materials, the present invention provides an organic hole injection material and its application.
[0005] The technical solution of the present invention is achieved in the following way: An organic hole injection material is provided, the general structural formula of which is as follows:
[0006]
[0007] Among them, X, Y, and Z are each independently selected from C, O, CO, S, Se, SO, SeO, SO2, or SeO2;
[0008] At least one of R1, R2, R3, and R4 is selected from F, CN, or The remainder is hydrogen.
[0009] Preferably, in one embodiment of the present invention, in the structural formula of the organic hole injection material, Y or Z are different, and one of Y or Z is C.
[0010] Preferably, in one embodiment of the present invention,
[0011] When Y = C, its general structural formula is:
[0012] When Z = C, its general structural formula is:
[0013] Preferably, in one embodiment of the present invention, at least two of R1, R2, R3, and R4 are selected from F, CN, or They are the same or different from each other.
[0014] Preferably, in one embodiment of the invention, the hydrogen in the molecular formula is partially or completely replaced by deuterium.
[0015] Preferably, in one embodiment of the invention, the organic hole injection material is represented by any of the following compounds:
[0016]
[0017]
[0018]
[0019]
[0020]
[0021]
[0022]
[0023]
[0024]
[0025]
[0026]
[0027] This invention also provides an organic light-emitting device based on a bis-pentacyclic ring derivative substituted with fluorine atoms, cyano groups, or pentafluorophenyl groups as the hole injection layer material. The bis-pentacyclic ring is selected from thiophene, furan, or selenophenol bis-pentacyclic ring groups. The specific structure of the device is, in sequence, a transparent substrate, an anode, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, an electron transport layer, and a cathode.
[0028] The transparent substrate can be glass or plastic.
[0029] The anode material is an inorganic material such as indium tin oxide, zinc oxide, or zinc tin oxide;
[0030] The hole injection layer material can be any of the above general formulas;
[0031] The hole transport layer material can be any of the following:
[0032]
[0033] Electron blocking layer materials can be used for
[0034]
[0035] The guest material in the luminescent layer can be BPH.
[0036] The hole-blocking layer material can be any of the following:
[0037]
[0038] The electron transport layer material can be any of the following:
[0039]
[0040] The electron injection layer can be lithium fluoride, Liq, etc.
[0041] The cathode material is aluminum, magnesium-silver alloy, etc.
[0042] The present invention also provides a perovskite solar cell comprising a cathode, an anode, and various organic layers; wherein the hole injection layer uses an organic hole injection material as described in any one of the foregoing.
[0043] The beneficial effects are as follows: The hole injection material provided by this invention is a double five-membered ring derivative substituted with electron-deficient groups. These double five-membered rings include, but are not limited to, thiophene, furan, or selenophenol double five-membered ring groups. The synthesis of such materials is relatively simple, which is beneficial for large-scale production; the material has suitable HOMO and LUMO energy level structures, which is conducive to carrier injection; the material's core of substituents and five-membered rings is beneficial for carrier transport in the device; and the material has high LUMO / HOMO energy levels, which is beneficial for transporting holes from the anode ITO to the hole transport layer.
[0044] The results of testing materials HOMO and LUMO show that the energy level structure of the material is suitable and can be used as a hole injection layer material for organic light-emitting devices.
[0045] The organic light-emitting diodes prepared using the hole injection layer material described above have high luminous efficiency and device lifetime. When applied to perovskite solar cells, they can improve photoelectric conversion efficiency and have high commercial value. Attached Figure Description
[0046] Figure 1 This is a schematic diagram of the structure of an organic light-emitting device using one embodiment of the present invention;
[0047] Figure 2 This is a schematic diagram of the structure of a perovskite solar cell using one embodiment of the present invention. Detailed Implementation
[0048] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments and corresponding drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0049] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Where specific experimental steps or conditions are not specified in the embodiments, they can be performed according to conventional experimental steps or conditions described in the literature in this field. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0050] Compounds for which no synthetic method is mentioned in this invention are all commercially available raw material products. The solvents and reagents used in this invention can be purchased from the domestic chemical market; additionally, those skilled in the art can synthesize them using well-known methods.
[0051] Example 1
[0052] The synthetic route for molecular formula 8 is shown below:
[0053]
[0054] The specific steps involved in synthesizing the compound are as follows:
[0055] Synthesis of intermediate M8: A chloroform solution (50 mL) containing liquid bromine (30 mL, 583 mmol) was added dropwise at 0 °C to a chloroform solution (50 mL) of thieno[3,2-b]thiophene (14.02 g, 100 mmol), and the addition was completed over 4 h. After the addition was complete, the reactants were heated to room temperature and then stirred under reflux for 3 h. A saturated aqueous solution of NaOH was then added to the reactants, and the mixture was stirred under reflux for 1 h to remove excess bromine. The mixture was extracted with chloroform, and the aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined, dried over anhydrous magnesium sulfate, and the organic solution was condensed under reduced pressure. The crude solid was recrystallized from a 1:1 (v / v) solution of chloroform and ethanol to give product M8 (43.30 g, 95% yield). 13 C NMR(100MHz,Chloroform-d)δ138.67,107.85,102.59.HRMS:[C6HBr4S2] + calculated:452.6253,found:452.6250.
[0056] Synthesis of Formula 8: M8 (22.79 g, 50 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to give the compound represented by Formula 8 (9.49 g, 79% yield). 13 C NMR(100MHz,Chloroform-d)δ148.40,116.81,113.20,112.75,104.79.HRMS:[C 10 HN4S2] + calculated:240.9643,found:240.9642.
[0057] Example 2
[0058] The synthetic route for molecular formula 100 is shown below:
[0059]
[0060] The specific steps involved in synthesizing the compound are as follows:
[0061] Synthesis of intermediate M100: A chloroform solution (50 mL) containing liquid bromine (30 mL, 583 mmol) was added dropwise at 0 °C to a chloroform solution (50 mL) containing selenophenol[3,2-b]selenophenol (23.40 g, 100 mmol), and the addition was completed over 4 h. After the addition was complete, the reaction mixture was heated to room temperature and then stirred under reflux for 3 h. A saturated aqueous solution of NaOH was then added to the reaction mixture, and the mixture was stirred under reflux for 1 h to remove excess bromine. The mixture was extracted with chloroform, and the aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined, dried over anhydrous magnesium sulfate, and the organic solution was condensed under reduced pressure. The crude solid was recrystallized from a 1:1 (v / v) solution of chloroform and ethanol to give product M8 (51.66 g, 94% yield). 13 C NMR(100MHz,Chloroform-d)δ157.57,133.44,124.44.HRMS:[C6HBr4Se2] + calculated:548.5142, found:548.5140.
[0062] Synthesis of molecular formula 100: M100 (27.48 g, 50 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain the compound represented by molecular formula 100 (12.53 g, yield 75%). 13 C NMR(100MHz,Chloroform-d)δ158.68,128.41,122.42,113.47,113.42.HRMS:[C 10 HN4Se2] + calculated:336.8532,found:336.8531.
[0063] Example 3
[0064] The synthetic route for molecular formula 24 is shown below:
[0065]
[0066] The specific steps involved in synthesizing the compound are as follows:
[0067] Synthesis of Formula 24: Formula 8 (4.81 g, 20 mmol) was weighed into a 150 mL single-necked flask, and 35% hydrogen peroxide solution (10 mL), water (20 mL), and acetone (20 mL) were added. The mixture was reacted in an ice-water bath for 6 hours. Saturated brine (50 mL) was added, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain the compound represented by Formula 24 (4.66 g, 91% yield). 13 C NMR(100MHz,Chloroform-d)δ144.41,143.38,122.14,119.99,119.55,118.52,112.96,112.86,112.38,110.74.HRMS:[C 10 HN4OS2] + calculated:256.9592,found:256.9591.
[0068] Example 4
[0069] The synthetic route for molecular formula 35 is shown below:
[0070]
[0071] The specific steps involved in synthesizing the compound are as follows:
[0072] Synthesis of Formula 35: Formula 8 (4.81 g, 20 mmol) was weighed into a 150 mL single-necked flask. Potassium permanganate (6.96 g, 44 mmol) was dissolved in 50 mL of water and then slowly added dropwise to the reaction flask. After the addition was complete, the reaction was stirred at room temperature for 24 hours. Saturated brine (50 mL) was added, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to give the compound represented by Formula 35 (4.75 g, 78% yield). 13 C NMR(100MHz,Chloroform-d)δ140.11,128.74,113.10,109.59,105.25.HRMS:[C 10 HN4O4S2] + calculated:304.9439,found:304.9436.
[0073] Example 5
[0074] The synthetic route for molecular formula 45 is shown below:
[0075]
[0076] The specific steps involved in synthesizing the compound are as follows:
[0077] Synthesis of intermediate M45: Thiophene[3,4-b]thiophene (14.02 g, 100 mmol) and NBS (19.58 g, 110 mmol) were placed in a 500 mL round-bottom flask and stirred overnight in an ice-water bath. After the reaction was complete, the mixture was washed with 1 N sodium thiosulfate aqueous solution, extracted with chloroform, washed three times with water, and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain product M45 (20.82 g, 95% yield). 1 H NMR(400MHz,Chloroform-d)δ7.93(d,1H),7.69(d,1H),7.55(t,1H). 13 C NMR(100MHz,Chloroform-d)δ141.52,136.48,125.14,123.05,119.67,109.59.HRMS:[C6H4BrS2] + calculated:218.8938,found:218.8935.
[0078] Synthesis of molecular formula 45: M45 (10.96 g, 50 mmol), cuprous cyanide (5.37 g, 60 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain the compound represented by molecular formula 45 (7.27 g, yield 88%). 1 H NMR(400MHz,Chloroform-d)δ8.03(d,1H),8.01(d,1H),7.66(t,1H). 13 C NMR(100MHz,Chloroform-d)δ142.84,136.52,128.92,123.64,120.53,114.74,108.49.HRMS:[C7H4NS2] + calculated:165.9785,found:165.9786.
[0079] Example 6
[0080] The synthetic route for molecular formula 63 is shown below:
[0081]
[0082] The specific steps involved in synthesizing the compound are as follows:
[0083] Synthesis of intermediate M63: 17.62 g (100 mmol) of 3,6-difluorothiopheno[3,2-b]thiophene and 39.2 g (220 mmol) of NBS were placed in a 500 mL round-bottom flask and stirred overnight in an ice-water bath. After the reaction was complete, the mixture was washed with 2N sodium thiosulfate aqueous solution, extracted with chloroform, washed three times with water, and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain product M63 (31.06 g, 93% yield). 13 C NMR(100MHz,Chloroform-d)δ140.52,127.82,92.59.HRMS:[C6HBr2F2S2] + calculated:332.7854,found:332.7853.
[0084] Synthesis of molecular formula 63: M63 (16.70 g, 50 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain the compound represented by molecular formula 63 (9.50 g, yield 84%). 13 C NMR(100MHz,Chloroform-d)δ151.86,134.50,107.75,93.55.HRMS:[C8HF2N2S2] + calculated:226.9549,found:226.9547.
[0085] Example 7
[0086] The synthetic route for molecular formula 189 is shown below:
[0087]
[0088] The specific steps involved in synthesizing the compound are as follows:
[0089] Synthesis of intermediate M189: Furano[3,2-b]furan (10.81 g, 100 mmol) and NBS (39.2 g, 220 mmol) were placed in a 500 mL round-bottom flask and stirred overnight in an ice-water bath. After the reaction was complete, the mixture was washed with 2N sodium thiosulfate aqueous solution, extracted with chloroform, washed three times with water, and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain product M189 (23.93 g, 90% yield). 1 H NMR(400MHz,Chloroform-d)δ6.94(s,2H). 13 C NMR(100MHz,Chloroform-d)δ147.52,123.36,97.44.HRMS:[C6H3Br2O2] + calculated:264.8500,found:264.8503.
[0090] Synthesis of molecular formula 189: M189 (13.29 g, 50 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain the compound represented by molecular formula 189 (6.32 g, 80% yield). 1 H NMR (400MHz, Chloroform-d) δ7.06 (s, 2H). 13 C NMR(100MHz,Chloroform-d)δ149.24,129.09,111.38,106.98.HRMS:[C8H3N2O2] + calculated:159.0195,found:159.0196.
[0091] Example 8
[0092] The synthetic route for molecular formula 209 is shown below:
[0093]
[0094] The specific steps involved in synthesizing the compound are as follows:
[0095] Synthesis of intermediate M209: Thiophene[3,2-b]furan (12.42 g, 100 mmol) and NBS (39.2 g, 220 mmol) were placed in a 500 mL round-bottom flask and stirred overnight in an ice-water bath. After the reaction was complete, the mixture was washed with 2N sodium thiosulfate aqueous solution, extracted with chloroform, washed three times with water, and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain product M209 (25.09 g, yield 89%). 1 H NMR(400MHz,Chloroform-d)δ7.34(s,1H),7.24(s,1H). 13 C NMR(100MHz,Chloroform-d)δ156.30,128.68,123.98,112.22,111.66,108.70.HRMS:[C6H3Br2OS] + calculated:280.8271,found:280.8270.
[0096] Synthesis of molecular formula 209: M209 (14.10 g, 50 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain the compound represented by molecular formula 209 (7.14 g, yield 82%). 1 H NMR(400MHz,Chloroform-d)δ7.57(s,1H),7.46(s,1H). 13 C NMR(100MHz,Chloroform-d)δ158.40,131.78,129.01,120.01,116.79,114.57,112.70,111.44.HRMS:[C8H3N2OS] + calculated:174.9966,found:174.9999.
[0097] Example 9
[0098] The synthetic route for molecular formula 246 is shown below:
[0099]
[0100] The specific steps involved in synthesizing the compound are as follows:
[0101] Synthesis of intermediate M246: A chloroform solution (50 mL) containing liquid bromine (13 mL, 250 mmol) was added dropwise at 0 °C to a chloroform solution (50 mL) containing 2,3-difluoroselenophenolo[3,2-b]thiophene (22.31 g, 100 mmol), and the addition was completed over 4 h. After the addition was complete, the reaction mixture was heated to room temperature and then stirred under reflux for 3 h. A saturated aqueous solution of NaOH was then added to the reaction mixture, and the mixture was stirred under reflux for 1 h to remove excess bromine. The mixture was extracted with chloroform, and the aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined, dried over anhydrous magnesium sulfate, and the organic solution was condensed under reduced pressure. The crude solid was recrystallized from a 1:1 (v / v) solution of chloroform and ethanol to give product M246 (35.04 g, 92% yield). 13 C NMR(100MHz,Chloroform-d)δ146.81,143.17,141.03,122.15,114.13,111.27.HRMS:[C6HF2Br2SSe] + calculated:380.7299,found:380.7296.
[0102] Synthesis of molecular formula 246: M246 (7.62 g, 20 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to give the compound represented by molecular formula 246 (4.75 g, yield 87%). 13 C NMR(100MHz,Chloroform-d)δ148.93,147.76,145.85,123.88,116.23,112.57,112.22,108.41.HRMS:[C8HF2N2SSe] + calculated:274.8994,found:274.8991.
[0103] Example 10
[0104] The synthetic route for molecular formula 267 is shown below:
[0105]
[0106] The specific steps involved in synthesizing the compound are as follows:
[0107] Synthesis of intermediate M267: Deuterated 3,6-difluoroselenophenolo[3,2-b]furan (17.31 g, 100 mmol) and NBS (39.2 g, 220 mmol) were placed in a 500 mL round-bottom flask and stirred overnight in an ice-water bath. After the reaction was complete, the mixture was washed with 2N sodium thiosulfate aqueous solution, extracted with chloroform, washed three times with water, and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain product M267 (28.12 g, yield 85%). 13 C NMR(100MHz,Chloroform-d)δ155.82,128.30,125.26,125.25,118.36,110.16.HRMS:[C6HD2Br2OSe] + calculated:330.7841,found:330.7839.
[0108] Synthesis of molecular formula 267: M267 (16.54 g, 50 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and reacted at 140 °C for 24 hours with stirring. After the reaction was complete, 20 mL of 1 N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 with saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to obtain the compound represented by molecular formula 267 (9.15 g, yield 82%). 13 C NMR(100MHz,Chloroform-d)δ157.64,134.15,131.77,125.56,119.16,116.96,115.29,111.39.HRMS:[C8HD2N2OSe] + calculated:224.9536,found:224.9531.
[0109] Example 11
[0110] The synthetic route for molecular formula 270 is shown below:
[0111]
[0112] The specific steps involved in synthesizing the compound are as follows:
[0113] Synthesis of intermediate M270: Thiophene[3,2-b]thiophene (14.02 g, 100 mmol) and NBS (39.2 g, 220 mmol) were placed in a 500 mL round-bottom flask and stirred overnight in an ice-water bath. After the reaction was complete, the mixture was washed with 2N sodium thiosulfate aqueous solution, extracted with chloroform, washed three times with water, and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography and collected. The product from the previous step (14.90 g, 50 mmol), cuprous cyanide (9.85 g, 110 mmol), and DMF (100 mL) were weighed into a 500 mL round-bottom flask and stirred at 140 °C for 24 hours. After the reaction was complete, 20 mL of 1N HCl solution was added, and the mixture was stirred at room temperature for 1 hour. The pH was adjusted to 7-8 by adding saturated potassium carbonate solution, and the mixture was extracted with chloroform. The aqueous phase was extracted three times with 100 mL of dichloromethane. The organic phases were combined and dried over anhydrous magnesium sulfate. The crude product was purified by silica gel column chromatography to give the compound represented by intermediate M270 (8.08 g, yield 85%). 1 H NMR (400MHz, Chloroform-d) δ7.86 (s, 2H). 13 C NMR (100MHz, Chloroform-d) δ143.39, 132.20, 114.45, 113.22.HRMS: [C8H3N2S2] + calculated:190.9738,found:190.9735.
[0114] Synthesis of M270: Under a nitrogen atmosphere and in anhydrous conditions, n-BuLi (27 mL, 67.5 mmol) was slowly added to 50 mL of a THF solution of M270 (9.49 g, 49.9 mmol) at 0 °C, and the mixture was stirred for 1 hour. Next, tri-n-butyltin chloride (19 mL, 70 mmol) was added to the reaction mixture, and the mixture was stirred at 0 °C for 30 minutes, then heated to room temperature and stirred for 12 hours. After simple filtration under nitrogen, THF was removed under vacuum and the mixture was loaded into 50 mL of toluene. This toluene solution was then transferred to a toluene solution of pentafluorobromobenzene (6 mL, 50 mmol) and tetra(triphenylphosphine)palladium (2.3 g, 1.9 mmol) in 40 mL, and the mixture was refluxed at 140 °C for 2 days. After cooling to room temperature, the mixture was filtered through a diatomaceous earth column with toluene. Finally, the toluene solutions were combined and concentrated, and recrystallized from chloroform to give the compound represented by molecular formula 270 (16.00 g, 90% yield). 1 H NMR(400MHz,Chloroform-d)δ7.86(s,1H). 13C NMR(100MHz,Chloroform-d)δ150.51(ddt),150.39(t),149.49(ddt),141.72,137.60(dtt), 135.72(dtt),131.93,128.08(tt),116.35,114.67,113.97,112.00(t),111.45(m).HRMS:[C 14 H2F5N2S2] + calculated:356.9580,found:356.9583.
[0115] Example 12
[0116] This invention provides organic light-emitting devices based on hole-injection materials composed of thiophene derivatives, furan derivatives, and selenophenol derivatives substituted with electron-deficient groups such as cyano, fluorine, and pentafluorophenyl. Figure 1 As shown, the metal cathode 191, electron injection layer 180, electron transport layer 160, light-emitting layer 150, hole transport layer 140, hole injection layer 130, anode 120 and glass substrate 110 are stacked sequentially from top to bottom. The device is fabricated by vapor deposition.
[0117] The metal cathode is made of aluminum, with a deposition rate of 0.1-0.3 nm / s and a thickness of 100 nm.
[0118] The electron injection layer uses the material synthesized in this patent and the commercially available hole injection material LMZ-2178, with a deposition rate of 0.05-0.1 nm / s and a thickness of 1 nm.
[0119] The electron transport layer is a compound LET003 with the following structure, with a deposition rate of 0.05-0.1 nm / s and a thickness of 40 nm;
[0120]
[0121] The light-emitting layer is formed by co-doping of a host material and a guest material. The host material is LBH001, which is currently commercially available. The guest material is LBD001 with the following structure. The mass ratio of the host material to the guest material is 90:10. The evaporation rate is 0.003-0.2 nm / s and the thickness is 40 nm.
[0122]
[0123] The electron blocking layer is a compound LEB001 with the following structure, with a deposition rate of 0.05-0.1 nm / s and a thickness of 10 nm.
[0124]
[0125] The hole transport layer is made of NPB compound with the following structure, with a deposition rate of 0.05-0.1 nm / s and a thickness of 100 nm.
[0126]
[0127] Anode 7 is made of indium tin oxide (ITO).
[0128] Table 1. Device Performance Table
[0129]
[0130] As shown in Table 1, the hole injection layer material provided by this invention produces devices with lower turn-on voltage, higher current efficiency, and longer lifetime compared to commercially available materials.
[0131] Example 13
[0132] This invention compares the HOMO and LUMO orbital energies of different materials with those of the commercially available LMZ-2178. It also compares the hole injection layer material of this invention with currently commercially available materials.
[0133] Table 2. Performance values of the material of this invention and commercial LMZ-2178
[0134]
[0135] The measured data shows that the hole injection layer material provided by this invention has deeper HOMO and LUMO energy levels and a slightly higher band width compared with commercial materials, which is more conducive to hole injection from the anode into the organic layer. This indicates that it can be better used in organic light-emitting devices to achieve better display effects.
[0136] In summary, the hole injection layer material provided by this invention can effectively improve the performance of organic light-emitting devices, including efficiency and lifespan, when applied to them.
[0137] Example 14
[0138] The perovskite solar cell structure provided in this embodiment is as follows: Figure 2 As shown, the specific preparation process is as follows:
[0139] ITO conductive glass was ultrasonically washed sequentially with acetone, deionized water, and isopropanol, and then dried under vacuum at 80°C for 12 hours. A hole injection layer was deposited on the ITO, followed by spin-coating of PTAA as a hole transport layer. A perovskite precursor solution was prepared, dissolved in DMSO, and spin-coated onto the PTAA film, then annealed at 100°C for 10 minutes. An electron transport layer solution was prepared by dissolving PCBM in chlorobenzene at a concentration of 10 mg / ml and spin-coating it onto the perovskite film. Then, a methanol solution of BCP was spin-coated onto the PCBM, and finally, a metallic silver electrode was deposited under vacuum.
[0140] The performance of the finally fabricated perovskite solar cell device is shown in Table 3 below:
[0141] none 1.12 21.68 68.17 16.55 Molecular formula 8 1.21 22.28 73.51 17.95 Molecular formula 24 1.18 22.37 77.78 20.15 Molecular formula 35 1.13 23.01 75.98 19.88 Molecular formula 45 1.10 22.58 79.54 21.35 Molecular formula 63 1.12 21.16 80.53 20.03 Molecular formula 100 1.17 22.33 74.05 20.55 Molecular formula 189 1.11 22.92 73.18 20.06 Molecular formula 209 1.15 22.86 79.21 19.68 Molecular formula 246 1.16 22.35 79.28 19.65 Molecular formula 267 1.15 22.89 79.35 19.87 Molecular formula 270 1.16 22.38 79.48 20.56
[0142] The organic hole-injection material structures listed above are only a partial representation. Other compounds with similar concepts, consisting of five-membered rings and strongly electron-withdrawing groups on the periphery, are all within the scope of this patent protection.
[0143] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. An organic hole injection material, characterized in that, Its general structural formula is as follows: Wherein, X and Y are each independently selected from S, Se, SO, SeO, SO2 or SeO2, and at least one of X and Y is selected from SO, SO2, SeO or SeO2; At least one of R1, R2, R3, and R4 is selected from F, CN, or The remainder is hydrogen.
2. The organic hole injection material according to claim 1, characterized in that, Represented by any of the following compounds: 。 3. An organic light-emitting device, characterized in that, It comprises a cathode, an anode, and various organic layers; wherein the hole injection layer uses the organic hole injection material according to any one of claims 1-2.
4. A perovskite solar cell, characterized in that, It comprises a cathode, an anode, and various organic layers; wherein the hole injection layer uses the organic hole injection material according to any one of claims 1-2.
Citation Information
Patent Citations
Semiconducting polymers
CN102149750A
Diketopyrrolopyrrole polymers for use in organic semiconductor devices
CN102362314A
Dithieno-cyclopentadiene polymer as well as preparation method and application thereof
CN114230770A
Method for producing heterocyclic aromatic compound having pentafluorophenyl group
JP2006076928A
Organic photoelectric conversion element and solar cell
JP2012234877A